Postinfectious irritable bowel syndrome in children - D.V. Pechkurov; A.A. Tyazheva (LCC «Medicine-Inform», 2021)
D.V. Pechkurov, A.A. Tyazheva Samara State Medical University, Samara, Russian Federation Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders in adults, children, and adolescents. This paper reviews the etiology and pathogenesis of IBS, particularly one of its subtypes, postinfectious IBS, associated with a prior acute intestinal infection. The authors discuss risk factors, diagnosis, and treatment for postinfectious IBS and describe diagnostic search and therapeutic algorithm in a child. Treatment for IBS involves changes in diet and lifestyle, pharmacotherapy, and psychotherapy.This case report is interesting for clinicians since only attempts are made to systematize guidelines on the diagnosis and treatment for postinfectious IBS. However, specific management strategies for this condition are scarce, making the diagnosis difficult and resulting in treatment delay. Keywords: irritable bowel syndrome, functional gastrointestinal disorders, prokinetic agent, synbiotic, Maxilac. For citation: Pechkurov D.V., Tyazheva A.A. Postinfectious irritable bowel syndrome in children. Russian Journal of Woman and Child Health. 2021;4(3):292-297 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-292-297.